Passing the baton? Handing over digital data from the project to operations - Whyte,JK; Lindkvist,C; Jaradat,S (Engineering Project Organization Journal, 2016)
From fieldwork conducted ahead of the London Olympic Games, we develop new understanding of how organizations hand over digital data from the project to operations. Prior research explains how practitioners negotiate meaning across boundaries in ongoing work. However, it gives little attention to hand-over, where one group disengages as another engages. We use the analogy of the baton pass in a relay race to articulate how hand-over requires attention to sequence, timing, passing technique and communication within a time-constrained window of opportunity. In our case study, the project delivery team transfer responsibility for sports venues and other facilities, and their associated digital data, to Games operators. We show how delivery professionals both project the nature of future work; and probe how meanings will be interpreted. They seek to extend the window to discuss and negotiate meaning with operators. Our study contributes to research on engineering projects and on the coordination of knowledge work by articulating the baton pass, window of opportunity and projection and probing activities involved in hand-over. Understanding and improving the hand-over of digital data from the project to operations is important to enable owners and operators to better manage built infrastructure.